Investigating the Replacement of the Physical Anti-scatter Grid with Digital Image Processing - Tromans, C; Diffey, J; Brady, M (2010)
Scattered photons degrade mammographic image quality, so, almost universally, a physical anti-scatter grid is used to limit their effect. Physical grids are not completely effective in rejecting only scattered photons, so patient dose must be increased in order to maintain low levels of quantum noise. The standard attenuation rate (SAR), a quantitative normalised representation of breast tissue for image analysis applications, incorporates a model of scatter, and a software correction of the image blurring arising from scatter within the image signal. A tissue equivalent phantom is used to investigate the possibility, in terms of both image sharpness and noise, of replacing the physical grid with the software correction in the SAR. Encouraging results are reported, software correction almost matching the performance of the grid, whilst maintaining a superior signal-to-noise ratio. © 2010 Springer-Verlag.